Fluorine-free super-hydrophobic sponge and preparation method thereof
By constructing a superhydrophilic coating with a multi-level structure of microspheres on the surface of melamine sponge and performing grafting reaction, superhydrophobic and super-oleophilic sponge materials were prepared, which solved the problems of high preparation costs and complex steps in the prior art, achieved efficient and low-cost large-scale preparation, and had excellent oil-water separation performance.
Patent Information
- Application Number
- CN202411979761.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
In the prior art, when preparing superhydrophobic sponges for oil-water separation, there are problems such as high cost, complex steps, strict preparation conditions, and difficult to prepare on a large scale.
A commercially available melamine sponge is used as the substrate, and a catechol-containing compound and an amino-containing silane coupling agent are used as co-deposition monomers to construct a superhydrophilic coating with a microsphere multi-level structure in a room temperature and a weakly alkaline environment, and a rough and low-surface energy hydrophobic coating is constructed through grafting reaction to realize the preparation of superhydrophobic and super-lipophilic sponge material.
This method simplifies the process flow, reduces costs, shortens preparation time, and can be promoted on a large scale. The sponge material has high oil absorption ratio for a variety of oil phases, and has excellent water repellency and stability.
Smart Images

Figure CN119798772A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional materials, and specifically refers to a fluorine-free super-hydrophobic sponge and a preparation method thereof. Background Art
[0002] With the rapid development of industry, the consumption of fossil fuels is increasing, which has also led to the frequent occurrence of oil spills. According to reports, more than 100,000 tons of oil leaked from tankers into the environment in 2018 alone, which has had a serious impact on the sustainable development of the ecosystem. The methods for treating oily wastewater include combustion, physical, chemical, and biological methods. Among them, the physical method is still a commonly used treatment method because it is simple, efficient, and environmentally friendly.
[0003] Inspired by lotus leaves, solid surfaces in the Cassie-Baxter state have excellent water repellency. The potential application of materials with special wettability in oil-water separation has attracted great attention from researchers, that is, nano-multilevel structures are constructed on substrates such as metal meshes, fabrics, sponges, and membranes, and modified with low surface energy materials for oil-water separation. Among them, sponges with three-dimensional porous structures have the characteristics of low cost, light weight, large porosity, extrudable and easy to recycle, and can be used as substrates to prepare special wettability materials.
[0004] According to three different wetting models of liquid on rough solid surfaces (Wenzel model, Cassie-Baxter model, and transition state model), the wetting state of the solid surface can be adjusted by constructing the roughness of the solid surface and changing the surface free energy. The surface modification technology to prepare materials with special wettability usually requires two steps: one is to construct a rough micro-nano structure on the solid surface, and the other is to use physical or chemical methods to reduce the surface energy.
[0005] For example, the invention patent CN116606477A in the prior art discloses a method for preparing a super-hydrophobic polyurethane sponge for oil-water separation, wherein a commercial polyurethane sponge is used as a substrate, and the sponge is modified by two-step continuous coating with polydopamine and graphene oxide, and then the graphene oxide on the sponge surface is reduced with a reducing agent to obtain the super-hydrophobic polyurethane sponge. Another example is the invention patent CN112029142B discloses a method for preparing an oil-absorbing hydrophobic sponge, wherein a silane coupling agent is used to modify a silica sol, and then a melamine sponge is added to the modified silica sol and stirred, and then the silica-modified sponge is mixed with a polytetrafluoroethylene emulsion and dimethylformamide and stirred, and finally the modified sponge product is obtained by vacuum drying at a high temperature of 200 to 300°C. In addition, according to the degree thesis "Preparation and Application of Hydrophobic Composite Materials Based on MOFs Modification", a super-hydrophobic and super-oleophilic porous composite material is prepared with a melamine formaldehyde sponge as a substrate. First, the sponge is surface-modified with polydopamine, and then a MOFs (MIL-53 (Fe)) coating is in situ grown in a high-pressure reactor through a solvent thermal reaction (150° C., 12 hours) to construct a rough structure, and finally n-dodecyl mercaptan molecules are grafted onto the surface to obtain the sponge product.
[0006] However, existing preparation methods have disadvantages such as high cost, complicated steps, harsh preparation conditions, and difficulty in large-scale preparation. Summary of the invention
[0007] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a fluorine-free super-hydrophobic sponge and a preparation method thereof, using a commercially available melamine sponge as a substrate, selecting a catechol-containing compound and an amino-containing silane coupling agent as a co-deposition monomer, imitating the Mussel-inspired strategy and combining surface mineralization, constructing a super-hydrophilic coating with a microsphere multi-level structure on the surface and inside of the sponge at room temperature and a weakly alkaline environment, and utilizing the abundant hydroxyl groups, amino groups and other active groups on the coating to carry out a grafting reaction with a low surface energy substance having a long-chain alkyl group, and finally obtaining a super-hydrophobic and super-oleophilic melamine sponge, the co-deposition modification is similar to the dopamine hydrophilic modification conditions, which are also room temperature and weakly alkaline conditions, but the modification time is greatly shortened, the cost is only a fraction of that of the dopamine hydrophilic modification, and the loading amount and the roughness of the coating are greatly increased, that is, a coating with a microsphere multi-level structure and a large number of active groups is constructed in one step, the method has a simple preparation process, a short process, mild conditions, and low cost, and is expected to be promoted on a large scale, effectively solving the problems in the current existing surface modification technology preparation technology:
[0008] 1) The cost of dopamine and graphene oxide is extremely high and cannot be prepared on a large scale;
[0009] 2) The three-step method requires high-temperature vacuum drying at 200-300°C. The steps are complicated, energy-intensive and costly;
[0010] 3) Three-step method: dopamine is extremely expensive, and the solvent thermal reaction requires a reactor, which makes it impossible to prepare on a large scale.
[0011] The technical solution adopted by the present invention for the above-mentioned technical problems is as follows: a super-hydrophobic and super-oleophilic sponge material is prepared by a two-step method under mild conditions using commercially available melamine sponge as a substrate, and a preparation method and application thereof are provided. A sponge material is obtained that can efficiently separate a layered oil-water mixture by adsorption.
[0012] In order to achieve the above object, the present invention provides a fluorine-free super-hydrophobic sponge and a preparation method thereof, comprising the following steps:
[0013] Step 1, configuration of the co-deposition system: the system is a mixture of Tris / ethanol, a catechol-containing monomer and a silane coupling agent are added, and stirred until completely dissolved;
[0014] Pretreatment of the substrate: ultrasonically clean the commercially available melamine sponge with water and ethanol respectively, and dry it for later use;
[0015] Step 2, primary modification of the sponge: soak the dried sponge in the co-deposition system, take it out, squeeze it several times, rinse it with deionized water, and then dry it;
[0016] Step 3, secondary modification of the sponge: soak the dried sponge modified in step 2 in an ethanol solution containing a long-chain alkane monomer, take it out and squeeze it several times, rinse it with anhydrous ethanol and dry it to obtain a super-hydrophobic and super-oleophilic modified sponge.
[0017] Furthermore, the step uses a commercially available melamine sponge as a substrate, the pore size of which is 40PPI to 60PPI.
[0018] Furthermore, in the Tris / ethanol mixed system in step 1, the Tris aqueous solution is 10 mM, and the volume ratio of Tris to ethanol is 3:1 to 1:3.
[0019] Furthermore, the catechol monomer in step 1 is preferably catechol.
[0020] Furthermore, the silane coupling agent in step 1 is preferably γ-aminopropyltriethoxysilane.
[0021] Furthermore, in the step 1, 1 to 4 g of catechol monomer is added to every 100 ml of Tris / ethanol mixed system in the co-deposition system, and the mass ratio of the silane coupling agent to the catechol monomer is 1:2 to 2:1.
[0022] Furthermore, in the step 2, the pretreated sponge is immersed in the co-deposition system for 10 to 24 hours at a temperature of 15 to 45°C.
[0023] Furthermore, the long-chain alkane-containing monomer in step three is preferably n-dodecyl mercaptan.
[0024] Furthermore, the mass fraction of the long-chain alkane monomer in step three is 0.5% to 2%.
[0025] Furthermore, in step three, the modification time is 12 to 36 hours and the temperature is 15 to 45°C.
[0026] The beneficial effects achieved by the present invention using the above structure are as follows:
[0027] 1. The present invention provides a sponge with special wettability prepared using a melamine sponge matrix. The special wettability refers to that the surface of the material has both large roughness and low surface energy. The surface of the modified sponge in water is in a Cassie-Baxter state, which has excellent water repellency. The oil phase under water or on the water surface can be effectively removed by utilizing this property. The modified sponge has a high oil absorption rate for a variety of oil phases or organic solvents. At the same time, the excellent compression resilience of the melamine sponge matrix and the stability of the coating can be utilized to allow for recycling.
[0028] 2. The sponge matrix provided by the present invention obtains a preparation method of a super-hydrophobic and super-oleophilic modified sponge by surface modification technology. A catechol-containing monomer and an amino-containing silane coupling agent are co-deposited in a mild environment to form a rough coating containing a large number of active groups such as hydroxyl groups and amino groups on the surface of the sponge skeleton. The active groups on the coating are then used to graft long-chain monomers with low surface energy to construct a rough and low-surface-energy hydrophobic coating, thereby achieving the purpose of preparing a super-hydrophobic sponge. This method avoids the high cost of dopamine, and has a simple preparation process, a short flow, and mild conditions, and is expected to be promoted on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A preparation flow chart of a fluorine-free super-hydrophobic sponge and a preparation method thereof proposed by the present invention;
[0030] Figure 2 Schematic diagram of the chemical mechanism of hydrophobic modification of the present invention;
[0031] Figure 3 The physical display diagram and water contact angle test results of the original melamine sponge, the modified sponge prepared in Comparative Example 1 and the water sponge prepared in Example 1 (cut open and re-photographed; supplementary contact angle diagram);
[0032] Figure 4Schematic diagram of the adsorption process of light oil (n-hexane) and heavy oil (dichloromethane) in water by the hydrophobic sponge prepared in Example 1;
[0033] Figure 5 The oil absorption ratio of the hydrophobic sponge prepared in Example 1 to different oils;
[0034] Figure 6 The scanning electron microscope comparison diagram of the original melamine sponge, the modified sponge prepared in Comparative Example 1 and the hydrophobic sponge prepared in Example 1;
[0035] Figure 7 This is a comparison chart of infrared spectra of the original melamine sponge, the modified sponge prepared in Comparative Example 1, and the hydrophobic sponge prepared in Example 1.
[0036] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0038] The following examples are summarized, material preparation:
[0039] Melamine sponge was purchased from Shanghai Zhenmo New Materials Co., Ltd. The reagents used in the modification: catechol (CA, analytical grade, 99.5%), pyrohexanoic acid (analytical grade), (3-aminopropyl) triethoxysilane (KH550, analytical grade, 99.5%), n-dodecanethiol (DT, 98%), dichloromethane (analytical grade), n-hexane (analytical grade), methyl acrylate (analytical grade) were purchased from Shanghai Yien Chemical Technology Co., Ltd., tris(hydroxymethylaminomethane) (Tris, analytical grade, 99.9%) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., anhydrous ethanol (analytical grade) was purchased from Hangzhou Gaojing Fine Chemical Co., Ltd. The engine oil used in the experiment was Mobil 1 produced by Exxon Mobil Corporation. TM Formula 0W-40. The rapeseed oil used in the experiment is Waipoxiang small-pressed rapeseed oil produced by Wilmar International Golden Dragon Fish Food Group Co., Ltd.
[0040] Embodiment 1:
[0041] Prepare a mixed solution of 200 ml with a volume ratio of Tris / ethanol of 1:1, wherein Tris is 10 mM (25°C, pH 8.5); add 2 g of catechol and stir until completely dissolved, then add 4 g of KH550 and stir for 5 min to prepare a co-deposition system solution; put the pretreated dry sponge into the mixed solution and completely immerse it, place it at 35°C for 14 hours, take it out and squeeze it several times, rinse it with deionized water and then dry it; then soak it in 100 ml of ethanol solution containing 1 g of DT, and perform secondary modification at 25°C for 24 hours; take it out and squeeze it several times, rinse it with ethanol and then dry it at 60°C to obtain a modified sponge.
[0042] Example 2
[0043] Prepare a mixed solution of 200 ml with a volume ratio of Tris / ethanol of 2:1, wherein Tris is 50 mM (25°C, pH 8.5); add 2 g of catechol and stir until completely dissolved, then add 2 g of KH550 and stir for 5 minutes to prepare a co-deposition system solution; put the pretreated dry sponge into the mixed solution and completely immerse it, place it at 25°C for 12 hours, take it out and squeeze it several times, rinse it with deionized water and then dry it; then soak it in 100 ml of ethanol solution containing 1 g of DT, and perform secondary modification at 35°C for 12 hours; take it out and squeeze it several times, rinse it with ethanol and then dry it at 60°C to obtain a modified sponge.
[0044] Example 3
[0045] Prepare a total of 200 ml of a mixed solution with a volume ratio of Tris / ethanol of 1:1, in which Tris is 50 mM (25°C, pH 8.5); add 2 g of catechol and stir until completely dissolved, then add 3 g of KH550 and stir for 5 min to prepare a co-deposition system solution; completely immerse the pretreated dry sponge in the mixed solution, place it at 25°C for 24 hours, take it out, squeeze it several times, rinse it with deionized water, and then dry it. Then soak it in 100 ml of an ethanol solution containing 2 g of DT, and perform secondary modification at 35°C for 24 hours; take it out, squeeze it several times, rinse it with ethanol, and then dry it at 60°C to obtain a modified sponge.
[0046] Example 4
[0047] Prepare a mixed solution of 200 ml with a volume ratio of Tris / ethanol of 1:1, wherein Tris is 50 mM (25°C, pH 8.5); add 2 g of pyrohexanoic acid and stir until completely dissolved, then add 1 g of KH550 and stir for 5 min to prepare a co-deposition system solution; place the pretreated dry sponge in the mixed solution and completely immerse it, place it at 25°C for 24 hours, take it out and squeeze it several times, rinse it with deionized water and then dry it; then soak it in 100 ml of ethanol solution containing 2 g of DT, and perform secondary modification at 35°C for 24 hours; take it out and squeeze it several times, rinse it with ethanol and then dry it at 60°C to obtain a modified sponge.
[0048] Comparative Example 1:
[0049] A total of 200 ml of a mixed solution with a volume ratio of Tris / ethanol of 1:1 was prepared, wherein Tris was 10 mM (25°C, pH 8.5); 2 g of catechol was added and stirred until completely dissolved, and then 4 g of KH550 was added and stirred for 5 minutes to prepare a co-deposition system solution; the pretreated dry sponge was placed in the mixed solution and completely immersed, and placed at 35°C for 14 hours. After taking out, it was squeezed several times, rinsed with deionized water, and then dried to obtain a modified sponge.
[0050] Comparative Example 2:
[0051] A total of 200 ml of a mixed solution with a volume ratio of Tris / ethanol of 1:1, wherein Tris is 10 mM (25°C, pH 8.5); 2 g of catechol is added and stirred until completely dissolved to prepare a modified solution; the pretreated dry sponge is placed in the mixed solution and completely immersed, placed at 35°C for 14 hours, taken out, squeezed and rinsed several times, and then dried; then immersed in 100 ml of an ethanol solution containing 1 g of DT, and modified twice at 25°C for 24 hours; taken out, squeezed and rinsed with ethanol several times, and then dried at 60°C to obtain a modified sponge.
[0052] Comparative Example 3:
[0053] Prepare a total of 200 ml of a mixed solution with a volume ratio of Tris / ethanol of 1:1, in which Tris is 10 mM (25°C, pH 8.5); add 4 g of silane coupling agent KH550 and stir for 5 minutes to prepare a modified solution; put the pretreated dry sponge into the mixed solution and completely immerse it, place it at 35°C for 14 hours, take it out, squeeze it and rinse it several times, and then dry it; then soak it in 100 ml of ethanol solution containing 1 g DT, and perform secondary modification at 25°C for 24 hours. Take it out, squeeze it several times, rinse it with ethanol, and dry it at 60°C to obtain a modified sponge.
[0054] Example 5 Wettability Test ( Figure 3 ):
[0055] Taking the original sponge, the samples prepared in comparative example 1 and embodiment 1 as examples, the modified samples were cut in the middle; water (methylene blue dyeing) and dichloromethane (oil red dyeing) were dropped onto the sample surface using a syringe; the water contact angle was tested using an optical contact angle meter (JY-82, Chengde Dingsheng Testing Machine Co., Ltd., China); the water contact angle was tested 3 times and the average value was taken to reduce the experimental error.
[0056] The wettability test results of the original sponge, the samples prepared in Comparative Example 1 and Example 1 are as follows: Figure 3As shown, the interior and surface of the modified sponge are modified, and the wettability is consistent. Except for Example 1 which has super hydrophobic and super oleophilic wettability, the original sponge and Comparative Example 1 are both super hydrophilic and super oleophilic.
[0057] Example 6 Water oil absorption performance test ( Figure 4 ):
[0058] Taking the sample prepared in Example 1 as an example, the oil sinking to the bottom of the water (dichloromethane, oil red dyeing) and the oil floating on the water surface (n-hexane, oil red dyeing) were tested for oil absorption performance.
[0059] The test results of the oil absorption performance of the sample prepared in Example 1 are as follows: Figure 4 As shown in Figure 2, the modified sponge has a good selective adsorption of the oil phase in water. Figure 4 As shown in (a), the modified sponge exhibits a silver mirror-like phenomenon underwater, which indicates that the surface of the modified sponge is in a Cassie-Baxter state and has excellent water-repellent properties.
[0060] Example 7 Oil absorption rate test ( Figure 5 ):
[0061] Taking the sample prepared in Example 1 as an example, different oil phases and organic solvents were subjected to adsorption tests. The specific method was to place the modified sponge into the above liquids, allow it to freely adsorb until saturated, take it out and weigh it again when there is no liquid dripping, and calculate the oil absorption rate according to formula (1):
[0062]
[0063] Where, represents the oil absorption ratio (g·g-1), ma and m0 are the masses (g) of the modified sponge after and before adsorption, respectively.
[0064] The results of the oil absorption test of the sample prepared in Example 1 are as follows Figure 5 As shown in the figure, it can be seen that the modified sponge has excellent oil storage capacity and can absorb oil or organic solvents 70-148 times its own weight. The difference in oil absorption rate is mainly due to differences in density, viscosity, volatility, etc. of the oil or organic solvent.
[0065] Example 8 Micromorphology Analysis ( Figure 6 ):
[0066] Taking the original sponge, the samples prepared in Comparative Example 1 and Example 1 as examples, the microscopic morphology of the sponge before and after modification was observed using a field emission scanning electron microscope (FESEM, Zeiss Ultra55, Germany).
[0067] The microscopic morphology results of the original sponge, comparative example 1 and embodiment 1 are as follows: Figure 6As shown in the figure, the original sponge is a highly connected three-dimensional porous material with a smooth and flat skeleton surface. After CK modification, a rough coating with a large number of microsphere structures appears on the surface of the sponge skeleton with obvious roughness, which provides structural conditions for the preparation of superhydrophobic materials. After secondary modification by DT, the rough coating structure on the sponge skeleton does not change significantly, which shows that the CK coating can remain stable during the DT modification process and maintain a multi-level structure with micro-nano size.
[0068] Example 9 Chemical Structure Characterization ( Figure 7 ):
[0069] Taking the original sponge, the samples prepared in Comparative Example 1 and Example 1 as examples, the chemical structure changes on the surface of the sponge before and after modification were tested using attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR, Nicolet is50, USA).
[0070] The infrared test results of the original sponge, the samples obtained in Comparative Example 1 and Example 1 are as follows: Figure 7 As shown, the antisymmetric stretching vibration peak of Si-O-Si appears at 1000-1100cm-1 (yellow shaded part), indicating that in the process of CA-KH550 forming the coating, there is hydrolysis and polycondensation of siloxane, forming Si-O bonds; the peaks at 2920cm-1 and 2842cm-1 are the stretching vibration peaks of -CH3 and -CH2 (purple shaded part); the peak type at 1460cm-1 becomes sharp, and the relative peak intensity increases; 1450-1650 is the bending vibration peak of the benzene ring. It is speculated that the change of the peak here is caused by the absorption peak of the benzene ring in the CK coating. The above shows that CA and KH550 are successfully co-deposited on the surface of the base fabric to form a coating. After secondary modification by DT, there is no obvious difference between the infrared spectrum and CK, which shows that the CK coating can remain relatively stable during DT modification. After DT modification, the stretching vibration peaks of the sample at 2920cm-1 and 2842cm-1 were significantly enhanced, which was caused by the CH stretching vibration on the saturated carbon (-CH3 and -CH2) in the molecule. The above shows that DT was successfully grafted onto the CK coating.
[0071] The present invention and its embodiments are described above, and such description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can design a structure and embodiment similar to the technical solution without creativity, which should belong to the protection scope of the present invention.
Claims
1. A fluorine-free super-hydrophobic sponge and a preparation method thereof, characterized in that: The following steps are involved: Step 1, configuration of the co-deposition system: the system is a mixture of Tris / ethanol, a catechol-containing monomer and a silane coupling agent are added, and stirred until completely dissolved; Pretreatment of the substrate: ultrasonically clean the commercially available melamine sponge with water and ethanol respectively, and dry it for later use; Step 2, primary modification of the sponge: soak the dried sponge in the co-deposition system, take it out, squeeze it several times, rinse it with deionized water, and then dry it; Step 3, secondary modification of the sponge: soak the dried sponge modified in step 2 in an ethanol solution containing a long-chain alkane monomer, take it out and squeeze it several times, rinse it with anhydrous ethanol and dry it to obtain a super-hydrophobic and super-oleophilic modified sponge.
2. The fluorine-free super-hydrophobic sponge and preparation method thereof according to claim 1, characterized in that: The step uses a commercially available melamine sponge as a substrate, and the pore size thereof is 40PPI to 60PPI.
3. The fluorine-free super-hydrophobic sponge and preparation method thereof according to claim 2, characterized in that: In the Tris / ethanol mixed system in step 1, the Tris aqueous solution is 10 mM, and the volume ratio of Tris to ethanol is 3:1 to 1:
3.
4. The fluorine-free super-hydrophobic sponge and preparation method thereof according to claim 3, characterized in that: The catechol monomer in the step 1 is preferably catechol.
5. The fluorine-free super-hydrophobic sponge and preparation method thereof according to claim 4, characterized in that: The silane coupling agent in the step 1 is preferably γ-aminopropyltriethoxysilane.
6. The fluorine-free super-hydrophobic sponge and preparation method thereof according to claim 5, characterized in that: The silane coupling agent in the step 1 is preferably γ-aminopropyltriethoxysilane.
7. The fluorine-free super-hydrophobic sponge and preparation method thereof according to claim 6, characterized in that: In the step 2, the pretreated sponge is immersed in the co-deposition system for 10 to 24 hours at a temperature of 15 to 45°C.
8. The fluorine-free super-hydrophobic sponge and preparation method thereof according to claim 7, characterized in that: The long-chain alkane-containing monomer in step three is preferably n-dodecyl mercaptan.
9. The fluorine-free super-hydrophobic sponge and preparation method thereof according to claim 8, characterized in that: The mass fraction of the long-chain alkane monomer in step 3 is 0.5% to 2%.
10. The fluorine-free super-hydrophobic sponge and preparation method thereof according to claim 9, characterized in that: Furthermore, in the step three, the modification time is 12 to 36 hours and the temperature is 15 to 45°C.
Citation Information
Patent Citations
A method for preparing an oil-absorbing and hydrophobic sponge and the oil-absorbing and hydrophobic sponge prepared therefrom.
CN112029142B
Preparation method of super-hydrophobic polyurethane sponge for oil-water separation
CN116606477A